Hate Speech Acts on Social Media (Forensic Linguistics Study) - Putri Lidiana Permata Sari; Lis Supiatman; Yen Aryni (English Teaching and Linguistics Journal (ETLiJ), 2022)
With the massive use of technology products such as social media, hate speech has become an inseparable part of society. In today's social life, social media has become a basic need to build social interaction. Human communication built with social media still involves language in various forms of writing. However, when it comes to interpersonal communication, social media users often don't realize that what they write can turn into hate speech. This study examined the phenomenon of using social media in the form of comments and statuses that lead to legal cases that were reviewed by using forensic linguistics. The research was conducted by reviewing the literature and observing documents regarding legal cases that occurred due to hate speech on social media.